2003
DOI: 10.2190/hd0a-n15l-rtfh-2du8
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Internet Search Strategies: Drawing upon Familiar Cognitive Paradigms When Accessing Electronic Information Sources

Abstract: The goal of this study was to evaluate and describe the Internet search strategies of adolescent learners. Participants were 161 middle and high school students. Collected data included students' descriptions of the search process, observations of student searching behaviors, and audit trail lists of search strings used by students. The students demonstrated three approaches for locating information on the Internet, seven methods for constructing search strings, and four techniques for recovering from unsucces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…We are only just beginning to understand the many new reading comprehension skills required on the Internet, and in many instances students do not know how to approach reading in online environments. For example, instead of reading the short descriptions provided in most search-engine results, students are most apt to begin with the first link provided and systematically work their way through the list (Guinee, Eagleton, & Hall, 2003). Not only is this time-consuming, but also it is not an effective strategy for locating relevant information.…”
Section: Reading On the Internetmentioning
confidence: 99%
“…We are only just beginning to understand the many new reading comprehension skills required on the Internet, and in many instances students do not know how to approach reading in online environments. For example, instead of reading the short descriptions provided in most search-engine results, students are most apt to begin with the first link provided and systematically work their way through the list (Guinee, Eagleton, & Hall, 2003). Not only is this time-consuming, but also it is not an effective strategy for locating relevant information.…”
Section: Reading On the Internetmentioning
confidence: 99%
“…Emerging research suggests a taxonomy of skills in 8 investigating search results. Firstly, a random (Guinee, Eagleton, & Hall, 2003) "click and look" (Leu et al, 2007) strategy with minimal reading of search results. Secondly, a limited strategic scrolling of search results (Dwyer, 2010) where each result, in turn, is systemically investigated.…”
Section: Generating Search Terms and Investigating Search Resultsmentioning
confidence: 99%
“…As expected the results of this study showed that professional web searchers are more powerful than their counterparts in locating relevant Web sites to their information needs. Another study by (Guinee et al, 2003) showed how teenagers use the well known cognitive schemas to search the internet. The analysis and discussion of their conducted study revealed that teenagers use three different approaches for locating information on the internet, four different ways to reformulate their unsuccessful queries, and seven methods to formulate their search strings.…”
Section: Related Workmentioning
confidence: 99%